Preparation method of modified LiFePO4 composite positive electrode material
By inlaiding graphene quantum dots between lithium iron phosphate material and carbon coating, the problems of low electronic conductivity and small lithium ion diffusion rate of lithium iron phosphate cathode material are solved, and its electrochemical performance is significantly improved, especially at low temperatures It exhibits excellent discharge specific capacity.
Patent Information
- Application Number
- CN202411373474.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-11
AI Technical Summary
The low electronic conductivity and small lithium ion diffusion rate of lithium iron phosphate cathode material lead to poor electrochemical performance, limiting its practical application in multiple fields.
Carbon fiber (CF) is used as the carbon source and graphene quantum dots (GQDs) are used as the conductive reinforcement. Graphene quantum dots are embedded between lithium iron phosphate and the carbon coating, and the synthesis and modification is carried out through the solvent thermal method and the high-temperature solid-phase sintering process. LiFePO4 composite positive electrode material.
The conductivity and lithium ion diffusion rate of lithium iron phosphate materials have been significantly improved, and their electrochemical properties such as magnification, circulation, charge and discharge are improved, especially at low temperatures, which show high discharge specific capacity.
Smart Images

Figure CN119419231A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new energy materials, lithium ion battery positive electrodes, and in particular relates to a method for preparing a modified LiFePO4 composite positive electrode material. Background Art
[0002] With the rise of energy storage technology, lithium-ion batteries (LIBs) have become an indispensable component of electric vehicles (EVs) and portable energy storage devices. As a key component of lithium-ion batteries, cathode materials have always been one of the most concerned research hotspots in the battery industry. Among them, orthorhombic olivine lithium iron phosphate (LiFePO4, theoretical capacity: 170mAh g -1 ) has become the most ideal cathode material for lithium-ion batteries due to its good cycle stability, high safety, low cost, and simple production process. However, the low electronic conductivity and slow ion diffusion rate of lithium iron phosphate in one-dimensional direction lead to its poor electrochemical performance, which also hinders its practical application in many fields.
[0003] As a positive electrode material for lithium-ion batteries, lithium iron phosphate has become the mainstream positive electrode material for lithium-ion batteries due to its many advantages such as high safety performance during charging and discharging and good cycle stability. Lithium iron phosphate belongs to the orthorhombic olivine structure and has excellent structural stability, but the defects of low electronic conductivity and low ion diffusion rate have affected its development. Therefore, the selection of suitable conductive materials plays a vital role in the use of lithium iron phosphate electrochemical performance.
[0004] Lithium iron phosphate has excellent electrochemical properties and is widely used in the following fields: Electric vehicles (EV): Due to its high safety and good thermal stability, lithium iron phosphate has become one of the main power batteries for electric vehicles; Energy storage systems: A large number of energy storage systems, such as household and industrial energy storage, use lithium iron phosphate batteries for energy balance and management; Power tools and portable electronic devices: Such as power tools, drones, etc., where safety and endurance requirements are high, lithium iron phosphate batteries are also often used.
[0005] The unit cell structure of lithium iron phosphate consists of a FeO6 octahedron, a PO4 tetrahedron and two symmetrical LiO6 octahedrons. On the one hand, the FeO6 octahedrons are connected by sharing vertices, and it is impossible to form a FeO6 octahedron sharing edge network, and thus it is impossible to continuously generate electronic conductive channels, resulting in a very low electronic conductivity of the entire lithium iron phosphate material (10 -9 ~ 10 -10 S cm -1 ). On the other hand, since the PO4 tetrahedron is located between the FeO6 octahedron and the LiO6 octahedron, the migration and diffusion of lithium ions in the lattice are hindered, resulting in a slow ion diffusion rate of the lithium iron phosphate material.
[0006] At present, there are many ways to solve the problem of electronic conductivity and diffusivity: such as surface coating (such as carbon nanotubes, high molecular conductive polymers), ion doping (transition metal cations such as Mn 4+ 、V 4+ 、Co 2+ or anion doping such as N, S, F), structural adjustment (porous structure design, nanoparticle refinement). Although some technological progress has been made, there are still many problems to achieve large-scale industrial production, and further exploration is still needed. Summary of the invention
[0007] The purpose of the present invention is to solve the problems of low electronic conductivity and low lithium ion diffusion rate of lithium iron phosphate positive electrode materials, and provide a preparation method of a modified LiFePO4 composite positive electrode material, using carbon fiber (CF) as a carbon source, graphene quantum dots (GQDs) as a conductive enhancer, and embedding graphene quantum dots between lithium iron phosphate and carbon coating to improve the material conductivity. The graphene quantum dot embedded LiFePO4 composite positive electrode material was synthesized by a solvothermal method in conjunction with a high-temperature solid-phase sintering process, and after a series of characterization tests, it was proved that the rate, cycle and other electrochemical properties of the modified lithium iron phosphate material were greatly improved.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a modified LiFePO4 composite positive electrode material, the method comprising:
[0010] S1. Dissolve the lithium source, phosphorus source and iron source in a solvent and stir them thoroughly for 3 to 6 hours to obtain a uniformly mixed yellow solution A;
[0011] S2, adding the prepared GQDs to the yellow solution A, and continuing to stir after ultrasonic dispersion to obtain solution B; the molar ratio of lithium source: phosphorus source: iron source: GQDs = 1:1:1:0-0.2;
[0012] S3, transferring solution B to a high-pressure hydrothermal reactor, and heat treating it at 180°C for 8-12 hours, and taking it out after cooling it to room temperature to obtain a mixed solution C;
[0013] S4, washing the mixed solution C with anhydrous ethanol for several times to remove other impurities, and then drying the washed sample under vacuum at 85°C for 12 hours, and then taking it out to obtain product D;
[0014] S5. Grind the product D in a mortar, mix it evenly with the carbon source in a mass ratio of 22 to 25:1, and finally calcine it at a high temperature in a quartz tube furnace to obtain the LFP@CF@GQD composite material.
[0015] Furthermore, in S1, the lithium source is one of lithium carbonate, lithium hydroxide, and lithium acetate; the phosphorus source is one of diammonium phosphate, phosphoric acid, and diammonium hydrogen phosphate; the iron source is one of ferrous oxalate dihydrate, ferric phosphate, ferric oxide, and ferric nitrate nonahydrate; and the solvent is one of soluble solvents such as acetone and DMF (N,N-dimethylformamide).
[0016] Furthermore, in S2, the stirring speed is 50-80 rpm, the temperature is 75-80°C, and the time is 2-8 hours.
[0017] Furthermore, in S3, the filling volume ratio of the hydrothermal reactor is 60-70% (70-80%).
[0018] Furthermore, in S4, when the mixed solution C is washed with anhydrous ethanol, the mixed solution should be stirred evenly at a rotation speed of 50-80 rpm.
[0019] Furthermore, in S5, the carbon source is one of carbon fiber, glucose, asphalt, and citric acid.
[0020] Furthermore, in S5, the atmosphere of the high temperature calcination is one of inert gases such as argon and nitrogen.
[0021] Furthermore, in S5, the heating rate of the high temperature calcination is 3-5°C / min.
[0022] Furthermore, in S5, the high temperature calcination time is 8 to 12 hours, and the sintering temperature is 600 to 750°C.
[0023] The beneficial effects of the present invention compared to the prior art are:
[0024] 1. The present invention improves the conductivity and diffusion rate of the LiFePO4 composite material by filling the gap between LiFePO4 and CF with graphene quantum dots.
[0025] 2. Using non-toxic, low-cost lithium carbonate, ammonium dihydrogen phosphate and ferrous oxalate dihydrate as raw materials, lithium iron phosphate composite materials are synthesized by hydrothermal reaction and high-temperature solid phase method, and the synthesis path is simple.
[0026] 3. Quasi-zero-dimensional carbon materials - graphene quantum dots (GQDs) can enhance the contact between carbon-coated LiFePO4 and CF, thereby improving the conductivity of lithium iron phosphate materials.
[0027] 4. The introduction of GQDs to modify lithium iron phosphate can improve the conductivity of the material itself while improving the lithium ion diffusion kinetics, thereby achieving excellent electrochemical properties such as rate, cycle, and charge and discharge.
[0028] 5. The main reason why LFP@CF@GQD composite material exhibits high discharge specific capacity at low temperature is that the introduction of GQDs with quantum tunneling effect and good electrical conductivity can improve the poor ionic conductivity and migration ability of lithium iron phosphate material at low temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 XRD diagrams of lithium iron phosphate materials of Example 1, Example 2, Example 3 and Comparative Example 1;
[0030] Figure 2 The cycle performance diagram of the lithium iron phosphate material of Example 1, Example 2, Example 3 and Comparative Example 1;
[0031] Figure 3 The figure is a rate performance diagram of the lithium iron phosphate materials of Example 1, Example 2, Example 3 and Comparative Example 1;
[0032] Figure 4 This is a scanning electron microscope image of the lithium iron phosphate material of Example 1;
[0033] Figure 5 This is a scanning electron microscope image of the lithium iron phosphate material of Comparative Example 1. DETAILED DESCRIPTION
[0034] The following will combine the contents in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention; it is obvious that the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] The present invention uses carbon fiber (CF) as a carbon source, and graphene quantum dots (GQDs) as a conductive enhancer embedded between LiFePO4 and CF. The LFP@GQDs material is synthesized by a solvothermal method, and CF is introduced as a carbon layer during high-temperature sintering, which greatly improves the conductivity and lithium ion diffusion kinetics of LiFePO4. After a series of characterizations and electrochemical performance tests, it is proved that the capacity and rate performance of the lithium iron phosphate material modified by the technical route of the present invention are improved. The present invention effectively solves the defects of low electronic conductivity and low ion diffusion rate faced by lithium iron phosphate materials. The improvement of this technology is to introduce graphene quantum dots between the lithium iron phosphate material and the carbon coating, and use the excellent conductivity and quantum effect of graphene quantum dots to improve the conductivity and ion diffusion capacity of the lithium iron phosphate material, and finally achieve the cycle, rate and capacity improvement effects of the lithium iron phosphate battery.
[0036] The present invention synthesizes a lithium iron phosphate composite material by a solvothermal method in conjunction with a high-temperature solid-phase sintering route. This method can adjust the morphology and structure of the material so that the synthesized lithium iron phosphate material has a more uniform morphology and a smaller particle size, which is beneficial to improving the electrochemical performance of the lithium iron phosphate material. In addition, the lithium iron phosphate material synthesized by the solvothermal method requires lower energy consumption and has the advantages of safety, environmental protection, and high purity. The present invention confirms that the introduction of GQDs can improve the conductivity of the lithium iron phosphate composite material, improve the ion diffusion dynamics during the cycle, and increase the capacity of the battery during the charge and discharge process. The modified lithium iron phosphate composite material has a first discharge specific capacity of 165.8mAh / g at a current density of 1C, and still exhibits a high capacity retention rate of 98.86% after 500 cycles.
[0037] Example 1
[0038] This embodiment provides a method for preparing a modified LiFePO4 composite positive electrode material, which is as follows:
[0039] (1) Weigh 0.02 mol lithium carbonate (Li2CO3), 0.02 mol ammonium dihydrogen phosphate (NH4H2PO4) and 0.02 mol ferrous oxalate dihydrate (FeC2O4·2H2O) and dissolve them in 30 mL acetone. Ultrasonication is carried out at 30 °C for 6 h and the ultrasonic power is 60 W to obtain solution A. Subsequently, 1 g of GQDs is introduced into solution A and stirred until it is completely dissolved to obtain a mixed solution B. The mixed solution B is then transferred to a high-pressure reactor for hydrothermal treatment (temperature 180 °C, time: 8 h). After the hydrothermal reaction is cooled to room temperature, the reactants are washed several times with anhydrous ethanol to remove other impurities. The obtained product B is then placed in a vacuum drying oven and dried at a temperature of 85 °C for 12 h.
[0040] (2) Grind 12.5g of the obtained product B thoroughly, add 0.5g of CF as a carbon source to improve the conductivity of the material, and mix it thoroughly. Then put it into a tube furnace for high-temperature sintering treatment, the sintering temperature is 700℃ (heating rate 5℃ / min), the time is 12h, and argon is introduced as a protective gas. After the reaction is completed, the product C obtained is a lithium iron phosphate composite material.
[0041] (3) Take 0.4 g of the lithium iron phosphate composite material obtained by the reaction, 0.05 g of the conductive agent (Superp), and 0.05 g of the binder (PVDF), mix them evenly in a mass ratio of 8:1:1, add N-methylpyrrolidone (NMP) as a solvent, and then assemble the battery (components include: positive electrode sheet, negative electrode sheet, diaphragm, gasket, spring sheet, electrolyte) after coating, rolling, and slicing, and test.
[0042] Example 2
[0043] This embodiment provides a method for preparing a modified LiFePO4 composite positive electrode material, which is as follows:
[0044] (1) Weigh 0.02 mol of lithium carbonate (Li2CO3), 0.02 mol of ammonium dihydrogen phosphate (NH4H2PO4) and 0.02 mol of ferrous oxalate dihydrate (FeC2O4·2H2O) and dissolve them in 30 mL of acetone, and ultrasonicate them at 30°C for 6 h and 60 W to obtain solution A. Then transfer solution A to a high-pressure reactor for hydrothermal treatment (temperature 180°C, time: 8 h). After the hydrothermal reaction is completed, wash the reactants several times with anhydrous ethanol to remove other impurities, and then dry the obtained product B in a vacuum drying oven at 85°C for 12 h.
[0045] (2) Grind 11.2g of the obtained product B thoroughly, add 0.5g of CF as a carbon source to improve the conductivity of the material, and further mix thoroughly. Then put it into a tube furnace for high-temperature sintering treatment, the sintering temperature is 700°C (heating rate 5°C / min), the time is 12h, and argon is introduced as a protective gas. After the reaction is completed, the product C obtained is a lithium iron phosphate composite material.
[0046] (3) Take 0.4 g of the lithium iron phosphate composite material obtained by the reaction, 0.05 g of the conductive agent (Superp), and 0.05 g of the binder (PVDF), mix them evenly in a mass ratio of 8:1:1, add N-methylpyrrolidone (NMP) as a solvent, and then assemble the battery (components include: positive electrode sheet, negative electrode sheet, diaphragm, gasket, spring sheet, electrolyte) after coating, rolling, and slicing, and test.
[0047] Example 3
[0048] This embodiment provides a method for preparing a modified LiFePO4 composite positive electrode material, which is as follows:
[0049] (1) Weigh 0.02 mol of lithium carbonate (Li2CO3), 0.02 mol of ammonium dihydrogen phosphate (NH4H2PO4) and 0.02 mol of ferrous oxalate dihydrate (FeC2O4·2H2O) and dissolve them in 30 mL of acetone, and ultrasonicate them at 30°C for 6 h and 60 W to obtain solution A. Then transfer solution A to a high-pressure reactor for hydrothermal treatment (temperature 180°C, time: 8 h). After the hydrothermal reaction is completed, wash the reactants several times with anhydrous ethanol to remove other impurities, and then dry the obtained product B in a vacuum drying oven at 85°C for 12 h.
[0050] (2) Grind 11.4g of the obtained product B thoroughly, add 0.5g of glucose as a carbon source to improve the conductivity of the material, and mix it thoroughly. Then put it into a tube furnace for high-temperature sintering treatment, the sintering temperature is 700°C (heating rate 5°C / min), the time is 12h, and argon is introduced as a protective gas. After the reaction is completed, the product C obtained is a lithium iron phosphate composite material.
[0051] (3) Take 0.4 g of the lithium iron phosphate composite material obtained by the reaction, 0.05 g of the conductive agent (Superp), and 0.05 g of the binder (PVDF), mix them evenly in a mass ratio of 8:1:1, add N-methylpyrrolidone (NMP) as a solvent, and then assemble the battery (components include: positive electrode sheet, negative electrode sheet, diaphragm, gasket, spring sheet, electrolyte) after coating, rolling, and slicing, and test.
[0052] Example 4
[0053] This embodiment provides a method for preparing a modified LiFePO4 composite positive electrode material, which is as follows:
[0054] (1) Weigh 0.02 mol of lithium carbonate (Li2CO3), 0.02 mol of ammonium dihydrogen phosphate (NH4H2PO4) and 0.02 mol of ferrous oxalate dihydrate (FeC2O4·2H2O) and dissolve them in 30 mL of acetone, and ultrasonicate them at 30°C for 6 h and 60 W to obtain solution A. Then transfer solution A to a high-pressure reactor for hydrothermal treatment (temperature 180°C, time: 8 h). After the hydrothermal reaction is completed, wash the reactants several times with anhydrous ethanol to remove other impurities, and then dry the obtained product B in a vacuum drying oven at 85°C for 12 h.
[0055] (2) Grind 11.2g of the obtained product B thoroughly, add 0.5g of asphalt as a carbon source to improve the conductivity of the material, and mix it thoroughly. Then put it into a tube furnace for high-temperature sintering treatment, the sintering temperature is 700℃ (heating rate 5℃ / min), the time is 12h, and argon is introduced as a protective gas. After the reaction is completed, the product C obtained is a lithium iron phosphate composite material.
[0056] (3) Take 0.4 g of the lithium iron phosphate composite material obtained by the reaction, 0.05 g of the conductive agent (Superp), and 0.05 g of the binder (PVDF), mix them evenly in a mass ratio of 8:1:1, add N-methylpyrrolidone (NMP) as a solvent, and then assemble the battery (components include: positive electrode sheet, negative electrode sheet, diaphragm, gasket, spring sheet, electrolyte) after coating, rolling, and slicing, and test.
[0057] Example 5
[0058] This embodiment provides a method for preparing a modified LiFePO4 composite positive electrode material, which is as follows:
[0059] (1) Weigh 0.02 mol of lithium carbonate (Li2CO3), 0.02 mol of ammonium dihydrogen phosphate (NH4H2PO4) and 0.02 mol of ferrous oxalate dihydrate (FeC2O4·2H2O) and dissolve them in 30 mL of acetone, and ultrasonicate them at 30°C for 6 h and 60 W to obtain solution A. Then transfer solution A to a high-pressure reactor for hydrothermal treatment (temperature 180°C, time: 8 h). After the hydrothermal reaction is completed, wash the reactants several times with anhydrous ethanol to remove other impurities, and then dry the obtained product B in a vacuum drying oven at 85°C for 12 h.
[0060] (2) Grind 11.5g of the obtained product B thoroughly, add 0.5g of citric acid as a carbon source to improve the conductivity of the material, and further mix it thoroughly. Then put it into a tube furnace for high-temperature sintering treatment, the sintering temperature is 700°C (heating rate 5°C / min), the time is 12h, and argon is introduced as a protective gas. After the reaction is completed, the product C obtained is a lithium iron phosphate composite material.
[0061] (3) Take 0.4 g of the lithium iron phosphate composite material obtained by the reaction, 0.05 g of the conductive agent (Superp), and 0.05 g of the binder (PVDF), mix them evenly in a mass ratio of 8:1:1, add N-methylpyrrolidone (NMP) as a solvent, and then assemble the battery (components include: positive electrode sheet, negative electrode sheet, diaphragm, gasket, spring sheet, electrolyte) after coating, rolling, and slicing, and test.
[0062] Example 6
[0063] This embodiment provides a method for preparing a modified LiFePO4 composite positive electrode material, which is as follows:
[0064] (1) Weigh 0.02 mol of lithium carbonate (Li2CO3), 0.02 mol of ammonium dihydrogen phosphate (NH4H2PO4) and 0.02 mol of iron phosphate (FePO4) and dissolve them in 30 mL of acetone, and ultrasonicate at 30°C for 6 h at an ultrasonic power of 60 W to obtain solution A. Then transfer solution A to a high-pressure reactor for hydrothermal treatment (temperature 180°C, time: 8 h). After the hydrothermal reaction is completed, wash the reactant several times with anhydrous ethanol to remove other impurities, and then place the obtained product B in a vacuum drying oven for drying at 85°C for 12 h.
[0065] (2) Grind 11.1g of the obtained product B thoroughly, add 0.5g of CF as a carbon source to improve the conductivity of the material, and mix it thoroughly. Then put it into a tube furnace for high-temperature sintering treatment, the sintering temperature is 700°C (heating rate 5°C / min), the time is 12h, and argon is introduced as a protective gas. After the reaction is completed, the product C obtained is a lithium iron phosphate composite material.
[0066] (3) Take 0.4 g of the lithium iron phosphate composite material obtained by the reaction, 0.05 g of the conductive agent (Superp), and 0.05 g of the binder (PVDF), mix them evenly in a mass ratio of 8:1:1, add N-methylpyrrolidone (NMP) as a solvent, and then assemble the battery (components include: positive electrode sheet, negative electrode sheet, diaphragm, gasket, spring sheet, electrolyte) after coating, rolling, and slicing, and test.
[0067] Example 7
[0068] This embodiment provides a method for preparing a modified LiFePO4 composite positive electrode material, which is as follows:
[0069] (1) Weigh 0.02 mol of lithium carbonate (Li2CO3), 0.02 mol of ammonium dihydrogen phosphate (NH4H2PO4) and 0.02 mol of ferric oxide (Fe2O3) and dissolve them in 30 mL of acetone. Ultrasonication is performed for 6 h to obtain solution A. Solution A is then transferred to a high-pressure reactor for hydrothermal treatment (temperature 180°C, time: 8 h). After the hydrothermal reaction is completed, the reactant is washed several times with anhydrous ethanol to remove other impurities. The obtained product B is then placed in a vacuum drying oven and dried at 85°C for 12 h.
[0070] (2) The obtained product B was fully ground and crushed, and 0.5 g of CF was added as a carbon source to improve the conductivity of the material, and then it was fully mixed. Then it was placed in a tube furnace for high-temperature sintering treatment, the sintering temperature was 700°C (heating rate 5°C / min), the time was 12h, and argon was introduced as a protective gas. After the reaction was completed, the product C obtained was a lithium iron phosphate composite material.
[0071] (3) Take 0.4 g of the lithium iron phosphate composite material obtained by the reaction, 0.05 g of the conductive agent (Superp), and 0.05 g of the binder (PVDF), mix them evenly in a mass ratio of 8:1:1, add N-methylpyrrolidone (NMP) as a solvent, and then assemble and test the battery after coating, rolling, and slicing.
[0072] Example 8
[0073] This embodiment provides a method for preparing a modified LiFePO4 composite positive electrode material, which is as follows:
[0074] (1) Weigh 0.02 mol of lithium carbonate (Li2CO3), 0.02 mol of ammonium dihydrogen phosphate (NH4H2PO4) and 0.02 mol of ferric nitrate nonahydrate (Fe(NO3)3·9H20)) and dissolve them in 30 mL of acetone. Ultrasonication is performed for 6 h to obtain solution A. Solution A is then transferred to a high-pressure reactor for hydrothermal treatment (temperature 180°C, time: 8 h). After the hydrothermal reaction is completed, the reactant is washed several times with anhydrous ethanol to remove other impurities. The obtained product B is then placed in a vacuum drying oven and dried at 85°C for 12 h.
[0075] (2) The obtained product B was fully ground and crushed, and 0.5 g of CF was added as a carbon source to improve the conductivity of the material, and then it was fully mixed. Then it was placed in a tube furnace for high-temperature sintering treatment, the sintering temperature was 700°C (heating rate 5°C / min), the time was 12h, and argon was introduced as a protective gas. After the reaction was completed, the product C obtained was a lithium iron phosphate composite material.
[0076] (3) Take 0.4 g of the lithium iron phosphate composite material obtained by the reaction, 0.05 g of the conductive agent (Superp), and 0.05 g of the binder (PVDF), mix them evenly in a mass ratio of 8:1:1, add N-methylpyrrolidone (NMP) as a solvent, and then assemble and test the battery after coating, rolling, and slicing.
[0077] Example 9
[0078] This embodiment provides a method for preparing a modified LiFePO4 composite positive electrode material, which is as follows:
[0079] (1) Weigh 0.02 mol of lithium carbonate (Li2CO3), 0.02 mol of phosphoric acid (H3PO4) and 0.02 mol of ferric nitrate nonahydrate (Fe(NO3)3·9H20)) and dissolve them in 30 mL of acetone. Ultrasonication is performed for 6 h to obtain solution A. Solution A is then transferred to a high-pressure reactor for hydrothermal treatment (temperature 180°C, time: 8 h). After the hydrothermal reaction is completed, the reactant is washed several times with anhydrous ethanol to remove other impurities. The obtained product B is then placed in a vacuum drying oven and dried at 85°C for 12 h.
[0080] (2) The obtained product B was fully ground and crushed, and 0.5 g of CF was added as a carbon source to improve the conductivity of the material, and then it was fully mixed. Then it was placed in a tube furnace for high-temperature sintering treatment, the sintering temperature was 700°C (heating rate 5°C / min), the time was 12h, and argon was introduced as a protective gas. After the reaction was completed, the product C obtained was a lithium iron phosphate composite material.
[0081] (3) Take 0.4 g of the lithium iron phosphate composite material obtained by the reaction, 0.05 g of the conductive agent (Superp), and 0.05 g of the binder (PVDF), mix them evenly in a mass ratio of 8:1:1, add N-methylpyrrolidone (NMP) as a solvent, and then assemble and test the battery after coating, rolling, and slicing.
[0082] Example 10
[0083] This embodiment provides a method for preparing a modified LiFePO4 composite positive electrode material, which is as follows:
[0084] (1) Weigh 0.02 mol of lithium carbonate (Li2CO3), 0.02 mol of diammonium hydrogen phosphate ((NH4)2HPO4) and 0.02 mol of ferric nitrate nonahydrate ((Fe(NO3)3·9H20)) and dissolve them in 30 mL of acetone. Ultrasonication is performed for 6 h to obtain solution A. Solution A is then transferred to a high-pressure reactor for hydrothermal treatment (temperature 180°C, time: 8 h). After the hydrothermal reaction is completed, the reactant is washed several times with anhydrous ethanol to remove other impurities. The obtained product B is then placed in a vacuum drying oven and dried at 85°C for 12 h.
[0085] (2) The obtained product B was fully ground and crushed, and 0.5 g of CF was added as a carbon source to improve the conductivity of the material, and then it was fully mixed. Then it was placed in a tube furnace for high-temperature sintering treatment, the sintering temperature was 700°C (heating rate 5°C / min), the time was 12h, and argon was introduced as a protective gas. After the reaction was completed, the product C obtained was a lithium iron phosphate composite material.
[0086] (3) Take 0.4 g of the lithium iron phosphate composite material obtained by the reaction, 0.05 g of the conductive agent (Superp), and 0.05 g of the binder (PVDF), mix them evenly in a mass ratio of 8:1:1, add N-methylpyrrolidone (NMP) as a solvent, and then assemble and test the battery after coating, rolling, and slicing.
[0087] Comparative Example 1
[0088] This embodiment provides a method for preparing a modified LiFePO4 composite positive electrode material, which is as follows:
[0089] (1) Weigh 0.02 mol of lithium carbonate (Li2CO3), 0.02 mol of ammonium dihydrogen phosphate (NH4H2PO4) and 0.02 mol of ferrous oxalate dihydrate (FeC2O4·2H2O) and dissolve them in 30 mL of acetone. Ultrasonication is performed for 6 h to obtain solution A. Solution A is then transferred to a high-pressure reactor for hydrothermal treatment (temperature 180°C, time: 8 h). After the hydrothermal reaction is completed, the reactant is washed several times with anhydrous ethanol to remove other impurities. The obtained product B is then placed in a vacuum drying oven and dried at 85°C for 12 h.
[0090] (2) The obtained product B is fully ground and crushed, and then placed in a tubular furnace for high-temperature sintering treatment. The sintering temperature is 700°C (heating rate is 5°C / min) for 12 hours, and argon is introduced as a protective gas. After the reaction is completed, the obtained product C is a lithium iron phosphate composite material.
[0091] (3) Take 0.4 g of the lithium iron phosphate composite material obtained by the reaction, 0.05 g of the conductive agent (Superp), and 0.05 g of the binder (PVDF), mix them evenly in a mass ratio of 8:1:1, add N-methylpyrrolidone (NMP) as a solvent, and then assemble and test the battery after coating, rolling, and slicing.
[0092] Comparative Example 2
[0093] This embodiment provides a method for preparing a modified LiFePO4 composite positive electrode material, which is as follows:
[0094] (1) Weigh 0.02 mol of lithium hydroxide (LiOH), 0.02 mol of ammonium dihydrogen phosphate (NH4H2PO4) and 0.02 mol of ferrous oxalate dihydrate (FeC2O4·2H2O) and dissolve them in 30 mL of acetone. Ultrasonication is performed for 6 h to obtain solution A. Solution A is then transferred to a high-pressure reactor for hydrothermal treatment (temperature 180°C, time: 8 h). After the hydrothermal reaction is completed, the reactant is washed several times with anhydrous ethanol to remove other impurities. The obtained product B is then placed in a vacuum drying oven and dried at 85°C for 12 h.
[0095] (2) The obtained product B is fully ground and crushed, and then placed in a tubular furnace for high-temperature sintering treatment. The sintering temperature is 700°C (heating rate is 5°C / min) for 12 hours, and argon is introduced as a protective gas. After the reaction is completed, the obtained product C is a lithium iron phosphate composite material.
[0096] (3) Take 0.4 g of the lithium iron phosphate composite material obtained by the reaction, 0.05 g of the conductive agent (Superp), and 0.05 g of the binder (PVDF), mix them evenly in a mass ratio of 8:1:1, add N-methylpyrrolidone (NMP) as a solvent, and then assemble and test the battery after coating, rolling, and slicing.
[0097] Comparative Example 3
[0098] This embodiment provides a method for preparing a modified LiFePO4 composite positive electrode material, which is as follows:
[0099] (1) Weigh 0.02 mol of lithium acetate (CH3COOLi), 0.02 mol of ammonium dihydrogen phosphate (NH4H2PO4) and 0.02 mol of ferrous oxalate dihydrate (FeC2O4·2H2O) and dissolve them in 30 mL of acetone. Ultrasonication is performed for 6 h to obtain solution A. Solution A is then transferred to a high-pressure reactor for hydrothermal treatment (temperature 180°C, time: 8 h). After the hydrothermal reaction is completed, the reactant is washed several times with anhydrous ethanol to remove other impurities. The obtained product B is then placed in a vacuum drying oven and dried at 85°C for 12 h.
[0100] (2) The obtained product B is fully ground and crushed, and then placed in a tubular furnace for high-temperature sintering treatment. The sintering temperature is 700°C (heating rate is 5°C / min) for 12 hours, and argon is introduced as a protective gas. After the reaction is completed, the obtained product C is a lithium iron phosphate composite material.
[0101] (3) Take 0.4 g of the lithium iron phosphate composite material obtained by the reaction, 0.05 g of the conductive agent (Superp), and 0.05 g of the binder (PVDF), mix them evenly in a mass ratio of 8:1:1, add N-methylpyrrolidone (NMP) as a solvent, and then assemble and test the battery after coating, rolling, and slicing.
[0102] Performance test: The positive electrode materials of the embodiment and the comparative example were made into button batteries and the electrochemical performance test was carried out on the high-performance battery testing system Neware. The test conditions were: voltage range: 2.5-4.2V, temperature: 25°C, current size: 1C. The results are shown in the following table:
[0103]
[0104]
[0105] It can be found from Table 1 that the material of Comparative Example 1 has poor conductivity due to the lack of conductive carbon coating, and the lithium ion transmission is slow during the charge and discharge process, resulting in poor electrochemical performance. Compared with Example 2, Example 1 proves that the introduction of GQDs can improve the conductivity of the lithium iron phosphate composite material, improve the ion diffusion dynamics during the cycle, and improve the capacity of the battery during the charge and discharge process. It can be found from Examples 2-5 that carbon fiber as a conductive carbon coating can improve the electronic conductivity of the lithium iron phosphate material and improve the charge transmission. By comparing Example 1, Comparative Examples 1-3, Examples 6-8 and Examples 9-10, it is shown that lithium carbonate, ammonium dihydrogen phosphate, and ferrous oxalate dihydrate as the best lithium source, phosphorus source, and iron source show the best cycle stability and rate performance.
[0106] In addition, the present invention also detects the crystal structure of the lithium iron phosphate composite material, such as Figure 1 As shown, through the XRD test, it can be found that the crystal diffraction peaks of the product correspond one-to-one with the standard card and do not contain other impurity peaks, indicating that the physical purity of the sample is high. Through the electron microscope test, it can be found that the surface of the lithium iron phosphate material is wrapped with a layer of conductive carbon coating, which can greatly improve the conductivity of the material. The final result shows that the peak intensity of the crystal diffraction peak of the lithium iron phosphate in Example 1 is sharper, indicating that its crystallinity is high, which is conducive to maintaining the stability of the crystal structure of the lithium iron phosphate material during long-term circulation.
[0107] The 1C cycle performance test was performed on four samples of Example 1, Example 2, Example 3 and Comparative Example 1. The results are as follows: Figure 2 As shown, after 500 cycles of charge and discharge, it can be found that the long cycle stability and discharge specific capacity of Example 1, Example 2 and Example 3 are higher than those of Comparative Example 1, and the lithium iron phosphate composite material of Example 1 has an initial discharge specific capacity of 165.8 mAh / g at a current density of 1C. After 500 cycles, it still exhibits a high capacity retention rate of 98.86%, which is superior to the cycle stability, discharge specific capacity and capacity retention rate exhibited by other samples. At the same time, the four samples of Example 1, Example 2, Example 3 and Comparative Example 1 were subjected to 0.2C, 1C, 2C, 5C, 10C and 30C rate performance tests, and were subjected to 5 charge and discharge cycles at each current density, and then gradually returned to 0.2C according to the current density from large to small (5 cycles at each current density). The final rate performance results are shown as follows. Figure 3 As shown. It can be found that the discharge specific capacity of the lithium iron phosphate samples of Example 1, Example 2, and Example 3 is better than that of Comparative Example 1 at both high current density and low current density, and Example 1 shows the best rate performance. The above results prove that embedding GQDs between the surface of lithium iron phosphate and the conductive carbon coating can improve the conductivity and charge transfer capacity of the material, which is beneficial to improving the capacity retention rate and coulomb efficiency of the battery.
[0108] Figure 4 The scanning electron microscope image of Example 1 is shown, from which it can be found that the surface of lithium iron phosphate is covered with a uniform CF conductive carbon layer, and the introduction of CF and GQDs on the surface of the material proves that the introduction of GQDs between lithium iron phosphate and the carbon coating can improve the lithium ion diffusion kinetics while improving the electrical conductivity of the material itself. Figure 2 The lithium iron phosphate composite material of Example 1 was shown to have an initial discharge specific capacity of 165.8 mAh / g at a current density of 1C, and still exhibited a high capacity retention rate of 98.86% after 500 cycles, which is superior to the cycle stability, discharge specific capacity and capacity retention rate exhibited by other samples, thereby achieving excellent electrochemical properties such as rate, cycle, and charge and discharge.
[0109] The samples of Example 1 and Comparative Example 1 were tested by scanning electron microscope. The results are as follows: Figures 4-5 As shown. It was found that coating a layer of conductive carbon coating on the surface of lithium iron phosphate material can greatly improve the conductivity of the material, while the agglomeration of lithium iron phosphate material particles without coating strategy is extremely serious, which is not conducive to the full infiltration of electrolyte, resulting in very slow ion migration and electron transmission, resulting in poor electrochemical reaction kinetics and low discharge specific capacity. At the same time, by comparing the four samples of Example 1, Example 2, Example 3 and Comparative Example 1, it can be found that the introduction of GQDs between lithium iron phosphate and carbon coating can improve the lithium ion diffusion kinetics while improving the conductivity of the material itself, thereby achieving excellent rate, cycle and charge and discharge and other electrochemical properties. Mainly attributed to the excellent conductivity and quantum size effect of GQDs, it becomes easy for lithium ions to diffuse at the grain boundaries of lithium iron phosphate, greatly improving the ion diffusion kinetics of lithium iron phosphate materials during the charge and discharge process.
[0110] The above is an exemplary implementation of the present application. It should be pointed out that for any ordinary technician familiar with the technical field, without departing from the purpose of the present invention, the specific parameters in the above embodiments can be changed to form multiple specific embodiments, which are all within the common variation range of the present invention.
Claims
1. A method for preparing a modified LiFePO4 composite positive electrode material, characterized in that: The method is: S1. Dissolve the lithium source, phosphorus source and iron source in a solvent and stir them thoroughly for 3 to 6 hours to obtain a uniformly mixed yellow solution A; S2, adding the prepared GQDs to the yellow solution A, and continuing to stir after ultrasonic dispersion to obtain solution B; The molar ratio of lithium source: phosphorus source: iron source: GQDs = 1:1:1:0-0.2; S3, transferring solution B to a high-pressure hydrothermal reactor, and heat treating it at 180°C for 8-12 hours, and taking it out after cooling it to room temperature to obtain a mixed solution C; S4, washing the mixed solution C with anhydrous ethanol for several times to remove other impurities, and then drying the washed sample under vacuum at 85°C for 12 hours, and then taking it out to obtain product D; S5. Grind the product D in a mortar, mix it evenly with the carbon source in a mass ratio of 22 to 25:1, and finally calcine it at a high temperature in a quartz tube furnace to obtain the LFP@CF@GQD composite material.
2. The method for preparing a modified LiFePO4 composite positive electrode material according to claim 1, characterized in that: In S1, the lithium source is one of lithium carbonate, lithium hydroxide, and lithium acetate; the phosphorus source is one of diammonium phosphate, phosphoric acid, and diammonium hydrogen phosphate; the iron source is one of ferrous oxalate dihydrate, ferric phosphate, ferric oxide, and ferric nitrate nonahydrate; and the solvent is one of soluble solvents such as acetone and DMF (N,N-dimethylformamide).
3. The method for preparing a modified LiFePO4 composite positive electrode material according to claim 1, characterized in that: In S2, the stirring speed is 50-80 rpm, the temperature is 75-80°C, and the time is 2-8 hours.
4. The method for preparing a modified LiFePO4 composite positive electrode material according to claim 1, characterized in that: In S3, the filling volume ratio of the hydrothermal reactor is 60-70% (70-80%).
5. The method for preparing a modified LiFePO4 composite positive electrode material according to claim 1, characterized in that: In S4, when the mixed solution C is washed with anhydrous ethanol, the mixed solution should be stirred evenly at a rotation speed of 50-80 rpm.
6. The method for preparing a modified LiFePO4 composite positive electrode material according to claim 1, characterized in that: In S5, the carbon source is one of carbon fiber, glucose, asphalt, and citric acid.
7. The method for preparing a modified LiFePO4 composite positive electrode material according to claim 1, characterized in that: In S5, the atmosphere of the high temperature calcination is one of inert gases such as argon and nitrogen.
8. The method for preparing a modified LiFePO4 composite positive electrode material according to claim 5, characterized in that: In S5, the heating rate of the high temperature calcination is 3-5°C / min.
9. The method for preparing a modified LiFePO4 composite positive electrode material according to claim 1, characterized in that: In S5, the high temperature calcination time is 8 to 12 hours, and the sintering temperature is 600 to 750°C.